Long-term athlete development information for parents (2018)
Informationen - in erster Linie für Eltern - zum langfristigen Leistungsaufbau (LLA) in Kanada. Dabei werden unter anderem die sieben Etappen des LLA des kanadischen Modells beschrieben. Long-Term Athlete Development Information for Parents What is LTAD? Getting an "Active Start" FUNdamentals Learn to Train Train to Train Train to Compete Train to Win Active for Life Links.